Alcohol and health in Central and Eastern European Union countries – status quo and alcohol policy options - Rehm, Jürgen; Štelemėkas, Mindaugas; Victoria Kim, Kawon; Zafar, Anush; Lange, Shannon (Journal of Health Inequalities, 2021)
The aim of this narrative review is to give an overview of alcohol consumption, attributable health harm, and potential alcohol control policies to reduce this harm in five Central and Eastern European Union countries: Czech Republic, Estonia, Latvia, Lithuania, and Poland. The overall level of alcohol consumption was high, with the two highest-consuming countries in the world being situated in Central and Eastern Europe (Czech Republic, Latvia), and all five of these countries being in the top 15% of World Health Organization member states with respect to consumption. Accordingly, alcohol-attributable health harm was high. Implementation of alcohol control policies could be improved, especially the implementation of pricing policies such as taxation increases. A moderate increase of the tax share on alcohol could result in thousands of lives being saved in Central and Eastern Europe in a single year. As taxation increases not only save lives, but also increase state revenue, the implementation of this alcohol control measure should be made a priority.